Partial Occlusion of a Third Nerve Palsy, a Shortcut through the Swedish Legal Vision Requirements for Driving. Issue 3 (3rd July 2021) - Lindström, Björn; Fridman, Åke
ABSTRACT: In this report, we present a case of a young woman with a traumatic third nerve palsy. A substantial practical dilemma for her was that according to the Swedish vision requirements for driving she was not allowed to drive due to diplopia within central 30 degrees of gaze. If she occluded the paretic eye to avoid diplopia, she would need to constantly occlude the eye for an adaptation period of six months before she would be allowed to drive with monocular vision. To get by this problem, the eyeglass of the paretic eye was partially occluded. In her case, this eliminated all diplopia within the central 30 degrees of gaze while she was still able to have binocular vision for primary gaze and horizontal gaze. This solution was accepted by the Swedish Transport Agency and she was allowed to drive without an adaptation period of 6 months. To our knowledge, this is the first time this solution is used for driving in Sweden.